(untitled) (Jurnal Bahasa, 2010)
This article aims to explain the current usage and continuance of the Pekan dialect in Pahang. The writer’s interest in this field of research was spurred by her random observation that most Malay speakers in Pekan spoke variations of Kelantanese, Terengganu, or standard Malay. The writer assumed that migration and language contact situations contributed to changes in the usage of Pekan’s original dialect. The dialect may be in a transitional stage as the native speakers’ linguistic repertoire increases with contact from other varieties of the Malay language. Economic and vocational factors also play an important role in the dialect’s usage. All three factors interact closely as a result of modernisation which leads individuals and communities to seek upward social mobility. The analysis in this article is based on lexical data gathered through interviews with Pekan speakers aged between 20 and 70. Notwithstanding possible limitations, data gathered is adequate to answer empirically the research questions postulated. Findings were related to concepts contained in the Social Network Model of Milroy (1980) and to changes in the economic, social status, demographic, and institutional support factors that form part of the discussion of language change by Giles et al. (1977) and Appel and Muysken (1987). The article contributes to the discourse on dialect studies in Malaysia and, specifically, to the status of the Pekan dialect, particularly with regard to the issue of language change and modernisation. Keywords: sosial network, vernacular, language change, perpetuation of language, network density